The Impact of Telehealth on Cancer-related Symptoms among Patients with Cancer: A Narrative review - I Made Cahyadi Agastiya; Endar Kurianto; Hanifati Akalili (Institut Citra Internasional, 2026)
Cancer remains one of the leading global health problems, contributing significantly to both morbidity and mortality worldwide. Cancer patients face not only invasive and prolonged treatments but also various cancer-related symptoms that affect their quality of life. Health care providers are therefore expected to innovate and deliver comprehensive care that facilitates the transition of post-cancer management from hospital to home and community settings. Telehealth has emerged as a potential solution to address these challenges. This study aimed to synthesis evidence on the impact of telehealth programs for self-management of cancer-related symptoms among cancer patients. This study employed a narrative review design. A narrative review was conducted using PubMed, EBSCOhost, ScienceDirect, CINAHL, and Springer databases. Inclusion criteria included quantitative studies involving cancer patients, published between 2015 and 2025, open-access, and containing self-management components related to cancer care. Qualitative studies, systematic reviews, study protocols, and pilot studies were excluded. A total of seven articles met the inclusion criteria and were analyzed. The findings indicate that telehealth interventions for patients with cancer—implemented through mobile health (mHealth) and web-based platforms—have a positive impact on patients’ stress reduction, anxiety, depression, fatigue, and fear of cancer recurrence, increasing physical activity, quality of life, adherence to care. Telehealth interventions show potential to improve access to care and support cancer patients in managing symptoms within the community. Future studies should explore the strengths and limitations of various telehealth modalities.